2022
DOI: 10.53450/2179-1465.rg.2022v13i2p73-80
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Photography: a review of the contextual knowledge of a PhD practice-led research project

Abstract: Despite its 35 years of academic presence, practice-led research is still in the process of building its status regarding definitions and its discourse. One of the fundamentals of this type of research is that practice-led expands the study to encompass questions that emerge from practice. Practice-led maintain the scientific, academic protocols and observing academic rigour, following structures and themes with the characteristics of rigour: the study goals, the methods for specific media and processes, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
11

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 12 publications
0
11
0
11
Order By: Relevance
“…This research project challenges the dualistic view and assumes that the physical body does not emerge as an isolated subject but is layered as a dynamic and vulnerable facet of understanding in both the mind and body (Mortensen Steagall, 2019;Mortensen Steagall & Ings, 2018). According to Wilson (2011), embodied cognition emphasizes the body's active role in shaping cognition and understanding an agent's mind and cognitive capacities.…”
Section: Embodimentmentioning
confidence: 99%
See 3 more Smart Citations
“…This research project challenges the dualistic view and assumes that the physical body does not emerge as an isolated subject but is layered as a dynamic and vulnerable facet of understanding in both the mind and body (Mortensen Steagall, 2019;Mortensen Steagall & Ings, 2018). According to Wilson (2011), embodied cognition emphasizes the body's active role in shaping cognition and understanding an agent's mind and cognitive capacities.…”
Section: Embodimentmentioning
confidence: 99%
“…A pesquisadora explorou e intuiu seu caminho usando caminhos internos e reconhecendo as pessoas vivas e habitantes do espaço. Nesse sentido, a investigação heurística é ativada por uma incorporação contínua na criação das saídas de design (Mortensen Steagall & Grieves, 2023;Mortensen Steagall, 2022;Mortensen Steagall, 2019;Mortensen Steagall, 2021).…”
Section: Pesquisa Heurísticaunclassified
See 2 more Smart Citations
“…This form of inquiry, epitomised by phenomenological reduction, provides intuitable the characteristic of consciousness as the meaning of the experience of the phenomenon (Mortensen Steagall, 2022;Mortensen Steagall & Ings, 2018). Husserl suggested that the phenomenological method is "the attempt to doubt everything has its place in the realm of our perfect freedom" (p.107).…”
Section: Phenomenologymentioning
confidence: 99%